The Study of Dupont Model and Financial Performance of Sharia Banks - Yoshanti, Ghita; Kurnia, Rahmat (TAMWIL : Jurnal Ekonomi Islam, 2024)
The financial performance of a bank can be evaluated through financial statement analysis using balance sheet, income statement, and ratio analysis. This research focuses on the financial performance of Islamic Commercial Banks in Indonesia for the period 2018-2022, using the DuPont System method. The interest in this study is the financial performance of Islamic banks in Indonesia as seen from the development of assets and net income as a whole experienced quite good growth from 2021 to 2022, although there are several Islamic banks that are still experiencing losses. The results of the analysis show that the best performance was achieved by Bank Aceh Syariah worth 158.26%, BPD West Nusa Tenggara Syariah worth 128.39%, Bank Mega Syariah worth 86.37%, Bank BCA Syariah worth 81.92%, BTPN Syariah worth 78.26%, Jabar Banten Syariah worth 30.31%, Bank Panin Dubai Syariah worth 12.36%, BMI worth 6.46%, Bank Aladin Syariah worth -0.002%, Bank Victoria Syariah worth -1.71% and Bank KB Bukopin Syariah worth 2.25%.  Of the eleven Islamic commercial banks, there are three banks whose average industry value is <0. This research provides a comprehensive overview of the performance ranking of Islamic Commercial Banks in Indonesia, as well as providing important insights for stakeholders to improve efficiency and competitiveness in the Islamic banking sector. This analysis is expected to be a reference in assessing the stability and financial growth potential of Islamic banks in the future.